Solution-combustion synthesis of doped TiO2 compounds and its potential antileishmanial activity mediated by photodynamic therapy - Lopera, A. A. [UNESP] (2018)
Photodynamic therapy has emerged as an alternative treatment for cutaneous leishmaniasis, and compounds with photocatalytic behavior are promising candidates to develop new therapeutic strategies for the treatment of this parasitic disease. Titanium dioxide TiO2 is a semiconductor ceramic material that shows excellent photocatalytic and antimicrobial activity under Ultraviolet irradiation. Due to the harmful effects of UV radiation, many efforts have been made in order to enhance both photocatalytic and antimicrobial properties of TiO2 in the visible region of the spectrum by doping or through modifications in the route of synthesis. Herein, Fe-, Zn-, or Pt- doped TiO2 nanostructures were synthesized by solution-combustion route. The obtained compounds presented aggregates of 100 nm, formed by particles smaller than 20 nm. Doping compounds shift the absorption spectrum towards the visible region, allowing production of reactive oxygen species in the presence of oxygen and molecular water when the system is irradiated in the visible spectrum. The Pt (EC50 = 18.2 ± 0.8 μg/mL) and Zn (EC50 = 16.4 ± 0.3 μg/mL) –doped TiO2 presented the higher antileishmanial activities under visible irradiation and their application as photosensitizers in photodynamic therapy (PDT) strategies for the treatment of cutaneous leishmaniasis should be considered.